Stromal expression of decorin, Semaphorin6D, SPARC, Sprouty1 and Tsukushi in developing prostate and decreased levels of decorin in prostate cancer. - Alexander Henke; O Cathal Grace; George R Ashley; Grant D Stewart; Antony C P Riddick; Henry Yeun; Marie O'Donnell; Richard A Anderson; Axel A Thomson (PLoS ONE)
Background and aim During prostate development, mesenchymal-epithelial interactions regulate organ growth and differentiation. In adult prostate, stromal-epithelial interactions are important for tissue homeostasis and also play a significant role in prostate cancer. In this study we have identified molecules that show a mesenchymal expression pattern in the developing prostate, and one of these showed reduced expression in prostate cancer stroma. Methodology and principal findings Five candidate molecules identified by transcript profiling of developmental prostate mesenchyme were selected using a wholemount in situ hybridisation screen and studied Decorin (Dcn), Semaphorin6D (Sema6D), SPARC/Osteonectin (SPARC), Sprouty1 (Spry-1) and Tsukushi (Tsku). Expression in rat tissues was evaluated using wholemount in situ hybridisation (postnatal day (P) 0.5) and immunohistochemistry (embryonic day (E) E17.5, E19.5; P0.5; P6; 28 & adult). Four candidates (Decorin, SPARC, Spry-1, Tsukushi) were immunolocalised in human foetal prostate (weeks 14, 16, 19) and expression of Decorin was evaluated on a human prostate cancer tissue microarray. In embryonic and perinatal rats Decorin, Semaphorin6D, SPARC, Spry-1 and Tsukushi were expressed with varying distribution patterns throughout the mesenchyme at E17.5, E19.5, P0.5 and P6.5. In P28 and adult prostates there was either a decrease in the expression (Semaphorin6D) or a switch to epithelial expression of SPARC, and Spry-1, whereas Decorin and Tsukushi were specific to mesenchyme/stroma at all ages. Expression of Decorin, SPARC, Spry-1 and Tsukushi in human foetal prostates paralleled that in rat. Decorin showed mesenchymal and stromal-specific expression at all ages and was further examined in prostate cancer, where stromal expression was significantly reduced compared with non-malignant prostate. Conclusion and significance We describe the spatio-temporal expression of Decorin, Semaphorin6D, SPARC, Spry-1 and Tsukushi in developing prostate and observed similar mesenchymal expression patterns in rat and human. Additionally, Decorin showed reduced expression in prostate cancer stroma compared to non-malignant prostate stroma.